MEGACRYSTS FROM THE GRIB KIMBERLITE PIPE (ARKHANGELSK PROVINCE, RUSSIA) - Kostrovitsky S.I.; Suvorova L.V.; Malkovets V.G.; Verichev E.M.; Garanin V.K. (My University, 2004)
The megacryst suite of the Grib kimberlite pipe (Arkhangelsk province, Russia) comprises garnet, clinopyroxene, magnesian ilmenite, phlogopite and garnet-clinopyroxene intergrowths. Crystalline inclusions, mainly of clinopyroxene and picroilmenite, occur in garnet megacrysts. Ilmenite is characterized by a wide range in the contents of MgO (10.6–15.5 wt.%) and Cr2O3 (0.7–8.3 wt.%). Megacryst garnets show wide variations in Cr2O3 (1.3–9.6 wt.%) and CaO (3.6–11.0 wt.%) but relatively constant MgO (15.4–22.3 wt.%) and FeO (5.2–9.9 wt.%). The pyroxenes also show wide variations in such oxides as Cr2O3, Al2O3 and Na2O (0.56–2.95; 0.86–3.25; 1.3–3.0 wt.%, respectively). The high magnesium and chromium content of all these minerals puts them together in one paragenetic group. This conclusion was confirmed by studies of the crystalline inclusions in megacrysts, which demonstrate similar variations in composition. Low concentration of hematite in ilmenite suggests reducing conditions during crystallization. P–T estimates based on the clinopyroxene geothermobarometer (Contrib. Mineral. Petrol. 139 (2000) 541) show wide variations (624–1208 °C and 28.8–68.0 kbars), corresponding to a 40–45 mW/m2 conductive geotherm. The majority of Gar-Cpx intergrowths differ from the corresponding monomineralic megacrysts in having higher Mg contents and relatively low TiO2. The minerals from the megacryst association, as a rule, differ from the minerals of mantle xenoliths, but garnets in ilmenite-bearing peridotite xenoliths are compositionally similar to garnet megacrysts. The common features of trace element composition of megacryst minerals and kimberlite (they are poor in Zr group elements) suggest a genetic relationship. The origin of the megacrysts is proposed to be genetically connected with kimberlite magma-chamber evolution on the one hand and with associated mantle metasomatism on the other. We suggest that, depending on the primary melt composition, different paragenetic associations of macro/megacrysts can be crystallized in kimberlites. They include: (1) Fe–Ti (Mir, Udachnaya pipes); (2) high-Mg, Cr (Zagadochna, Kusova pipes); (3) high-Mg, Cr, Ti (Grib pipe).
Keywords: Kimberlite; Megacrysts; High-chromium association; Genesis